Guru Tegh Bahadur - Singh, Daljeet, Sir, Raja (Language Dept., Punjab, 1971)
On the life and teachings of Tegh Bahadur, 1621-1675, 9th guru of the Sikhs; includes English translation of some of his verses (with commentary), earlier published as a separate work.